Inflammatory breast cancer: High incidence of GCC haplotypes (−1082A/G, −819T/C, and −592A/C) in the interleukin-10 gene promoter correlates with over-expression of interleukin-10 in patients' carcinoma tissues. Issue 7 (July 2017) - Sabet, Salwa; El-Sayed, Shrouk Khalaf; Mohamed, Hossam Taha; El-Shinawi, Mohamed; Mohamed, Mona M
Interleukin-10 is involved in carcinogenesis by supporting tumor escape from the immune response. The aim of this study was to assess the single nucleotide polymorphisms, −1082A/G, −819T/C and −592A/C, in interleukin-10 gene promoter in inflammatory breast cancer compared to non–inflammatory breast cancer and association of these polymorphisms with interleukin-10 gene expression. We enrolled 105 breast cancer tissue (72 non–inflammatory breast cancer and 33 inflammatory breast cancer) patients and we determined the three studied single nucleotide polymorphisms in all samples by polymerase chain reaction restriction fragment length polymorphism and investigated their association with the disease and with various prognostic factors. In addition, we assessed the expression of interleukin-10 gene by real-time quantitative reverse transcription polymerase chain reaction and the correlation between studied single nucleotide polymorphisms and interleukin-10 messenger RNA expression. We found co-dominant effect as the best inheritance model (in the three studied single nucleotide polymorphisms in non–inflammatory breast cancer and inflammatory breast cancer samples), and we didn't identify any association between single nucleotide polymorphisms genotypes and breast cancer prognostic factors. However, GCC haplotype was found highly associated with inflammatory breast cancer risk (p < 0.001, odds ratio = 43.05). Moreover, the expression of interleukin-10 messenger RNA was significantly higher (p < 0.001) by 5.28-fold and 8.95-fold than non–inflammatory breast cancer and healthy control, respectively, where GCC haplotype significantly increased interleukin-10 gene expression (r = 0.9, p < 0.001).